Environmental Awareness of Government and Non-Government College Students of Chandigarh. (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
The present investigation is carried out to study the Environmental Awareness of Government and Non-Government College Students of Chandigarh. The sample consisted of 200 (100 male and 100 female) govt. And non-govt. College students of Chandigarh. The investigator has used. Self-prepared standardized Environmental Awareness Questionnaire (EAQ) for collection of data. The data collected was processed for statistical analysis through a t-test. There was no significant difference between boy and girl college students with regard to their Environmental Awareness (EA). A significant difference in the EA scores was found in the government and non-government college students of Chandigarh at 0.05 level, which was in favour of non-govt. College students. Also, significant difference was found in the level of EA of college students living in the rural and urban areas of Chandigarh favouring the urban group.